Incorporating Wordtune in EFL: Investigation of Effect on Students’ Writing Competency and Writing Engagement - Pridayani, Kadek; Hery Santosa, Made; Budasi, I Gede (Riviera Publishing, 2025)
Artificial Intelligence (AI)-based writing tools, such as Wordtune, are increasingly used in foreign language learning. Despite the growing importance of these digital tools, research on how AI-driven applications affect Indonesian students' writing in English as a Foreign Language (EFL) and their writing engagement remains limited. This study aims to examine the effect of Wordtune on students’ writing performance and explore their writing engagement. An explanatory sequential mixed-methods approach was employed, involving a writing test and interviews to collect data from 136 eighth graders, with 68 students in both the experimental and control groups. Both the writing test and interview guide were validated for content by two expert judges, while the post-test underwent empirical validity and reliability testing using data from 34 non-sample participants. The writing test data were analyzed using an independent t-test, and the interview data were examined through theoretical thematic analysis. The results showed a significant effect of Wordtune on students’ writing competency. Furthermore, students demonstrated active engagement across affective, behavioral, cognitive, and social domains. In conclusion, several implications regarding the implementation of AI writing tools in English language teaching are discussed.